Perceived environmental uncertainty, business strategy, balanced scorecard and organisational performance in selected manufacturing companies in Jordan - Abu-Allan, Almothanna Jamil (2018)
The turmoil in the Arab region and the so-called “Arab Spring” have overwhelmed many aspects in the region. The Jordanian economy has been affected mainly by the situation specifically in regard to the manufacturing sector. Several challenges have hindered the economic growth and the profitability of organisations within the sector. Such challenges include the massive immigration of refugees, the instability in import and export, the drop in demand, and environmental uncertainty. Therefore, the performance of the manufacturing sector in Jordan has declined over the last few decades due to the instability in the Arab region countries. Yet, the lack of information needed to make strategic decisions among manufacturing companies in Jordan is perhaps attributed to their ineffective implement of performance management systems. Many companies in the manufacturing sector in Jordan have adopted performance measurement systems rather than performance management systems, e.g. Balanced Scorecard (BSC), to achieve a competitive advantage and better performance. In order to better understand the performance management systems; this study utilises the contingency theory theoretical framework to examine the contingent relationships between several contingent factors and the implementation of BSC as a performance management system. The contingent factors consist of perceived environmental uncertainty and business strategy. This study examines the influence of perceived environmental uncertainty on business strategy, BSC implementation, and organisational performance. The influences of business strategy on BSC implementation, as well as, organisational performance were examined. The mediating role of BSC was also examined. 400 questionnaires were distributed to manufacturing companies in Jordan. A total of 312 usable responses were received representing a response rate of 78%. Structural Equation Modelling (SEM) using AMOS was then used to test eight hypotheses constructed from the conceptual framework of the study. SEM analysis revealed that: a) perceived environmental uncertainty has a positive influence on business strategy, BSC implementation, and organisational performance; b) business strategy has a positive influence on BSC implementation; c) business strategy does not have positive influence on organisational performance; d) the implementation of BSC has a positive influence on organisational performance; On the other hand, the implementation of BSC has a partial mediation role in the relationship between perceived environmental uncertainty and organisational performance. In contrast, the implementation of BSC has a full mediation role in the relationship between business strategy and organisational performance. Theoretically, the framework of this study provided important contributions to the literature of management accounting by considering contingent factors such as perceived environmental uncertainty and business strategy on the implementation of BSC. Findings of the study enhance the understanding of contingent factors that could influence the BSC implementation among manufacturing companies in Jordan. Besides, this study also assists companies to understand the need to implement BSC effectively in order to use relevant information for decision-making purposes, which in turn, should improve overall organisational performance.